PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI BEI - Mahariana, I Dewa Gede Pingga; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 7 No 3 (2014), 2014)
The inconsistency of the results of previous studies on the effect of managerial ownership and institutional ownership on earnings management is becoming an interest to do research again. The aim of this study was to reexamine the effect of managerial ownership and institutional ownership on earnings management. Earnings management as measured by discretionary accruals estimated by the Modified Jones Model. Manufacturing sector selected as the study sample. The test results by using multiple linear regression analysis proves that managerial ownership proved to negatively affect earnings management. Meanwhile, the test results are not shown to affect institutional ownership These test results prove the low value of accruals with high managerial ownership.
Keywords: managerial ownership, institutional ownership, discretionary accruals,